Dialkyl cobalt catalysts and their use for hydrosilylation and dehydrogenative silylation - CHIRIK PAUL; DIAO TIANNING; DELIS JOHANNES; ROY AROOP; LEWIS KENRICK (2017)
Disclosed herein are dialkyi cobalt complexes containing pyridine di-imine ligands and their use as catalysts for hydrosilylation, dehydrogenative silytation, and/or crosslinking processes. The present invention provides dialkyi cobalt complexes. More specifically, the invention provides dialkyt cobalt pyridine diimine complexes substituted with alkyl or alkoxy groups on the imine nitrogen atoms. The cobalt complexes can be used as catalysts for hydrosilylation and/or dehydrogenative silylation processes. 本发明公开了含吡啶二亚胺配体的二烷基钴配合物和它们用于氢化硅烷化、脱氢硅烷化和/或交联过程的催化剂的用途。本发明提供了二烷基钴配合物。更特别地，本发明提供了在亚胺氮原子上被烷基或烷氧基取代的二烷基钴吡啶二亚胺配合物。所述钴配合物可用作氢化硅烷化和/或脱氢硅烷化过程的催化剂。